KAJIAN DESAIN BANDARA INDONESIA: KENUSANTARAAN DITINJAU DARI POLA RUANG, SOSOK, DAN ORNAMENTASI - Andrew Darsono, Antonio; Prijotomo, Josef (Riset Arsitektur (RISA), 2025)
Abstract - The airport is a form of representation of the entry gate of a nation that is present as the first greeterfor users of air transportation modes, both domestic and international users. The representation of the gatesymbolizes the identity and image of a nation. Indonesian airports carry an important message about theidentity of a nation which is reflected through the architectural form of the airport. The airport was designed notonly as a fulfillment of the facilities of a region or even a country, but more than that, the airport is nowdesigned by placing ef orts to create a visual character that shows architectural styles both from the west to theeast of the Republic of Indonesia. This style reflects the potential of arts and culture, tourism, and local wisdom.The development of Indonesian architecture from the past to the present has resulted in transformationsof forms that are constantly adapting, Nusantara Architecture has emerged as an "other" science in viewingarchitecture. Nusantara architecture develops, transforms, and goes global, not imitating the past or existingones, while respecting the architecture of the past. The definition of Nusantara Architecture used is based onNusantara Architecture by Prof. Josef Prijotomo.Airports in Indonesia on an international scale no longer represent the city, but represent the face ofIndonesia. Terminal 3 of Soekarno Hatta International Airport, I Gusti Ngurah Rai International Airport, andSultan Hasanuddin International Airport have the highest number of users in Indonesia and play an importantrole as representatives of Indonesia. A descriptivequalitative-comparative comparison is made to see how the archipelagic aspects based on the definition ofArchipelago Architecture are applied to the three study object airports. So that it can be seen how thetransformation of Archipelago architectural knowledge has been attached to the design of airports in Indonesia.This study was conducted to find out how the process of updating archipelago architecture in airport buildingsin Indonesia, whether airports in Indonesia can reflect their Nusantara through spatial patterns, figures, andornamentation.Key Words: Airport, Nusantara Architecture, Visual Character, Spatial form, Shape, Ornamentation